Climate and structure of the 8.2 ka event reconstructed from three speleothems from Germany - Waltgenbach, Sarah; Scholz, Denis; Spötl, Christoph; Riechelmann, Dana; Jochum, Klaus P.; Fohlmeister, Jens; Schröder-Ritzrau, Andrea (Global and planetary change, 2020)
The most pronounced climate anomaly of the Holocene was the 8.2 ka cooling event. We present new 230Th/U-ages as well as high-resolution stable isotope and trace element data from three stalagmites from two different cave systems in Germany, which provide important information about the structure and climate variability of the 8.2 ka event in central Europe. In all three speleothems, the 8.2 ka event is clearly recorded as a pronounced negative excursion of the δ18O values and can be divided into a ‘whole event’ and a ‘central event’. All stalagmites show a similar structure of the event with a short negative excursion prior to the ‘central event’, which marks the beginning of the ‘whole event’. The timing and duration of the 8.2 ka event are different for the individual records, which may, however, be related to dating uncertainties. Whereas stalagmite Bu4 from Bunker Cave also shows a negative anomaly in the δ13C values and Mg content during the event, the two speleothems from the Herbstlabyrinth cave system do not show distinct peaks in the other proxies. This may suggest that the speleothem δ18O values recorded in the three stalagmites do not primarily reflect climate change at the cave site, but rather large-scale changes in the North Atlantic. This is supported by comparison with climate modelling data, which suggest that the negative peak in the speleothem δ18O values is mainly due to lower δ18O values of precipitation above the cave and that temperature only played a minor role. Alternatively, the other proxies may not be as sensitive as δ18O values to record this centennial-scale cooling event. This may particularly be the case for speleothem δ13C values as suggested by comparison with a climate modelling study simulating vegetation changes in Europe during the 8.2 ka event. Based on our records, it is not possible to resolve which of these hypotheses is most appropriate, but our multi-proxy dataset shows that regional climate evolution during the event was probably complex, although all δ18O records show a clear negative anomaly.
Gesehen am 14.12.2020